Kemampuan Regulasi Emosi dan Self Awareness Sebagai Prediktor Kecemasan pada Support Buddy di Lisa Helpline Provinsi Bali - Ni Luh Resmiadi; Ni Ketut Jeni Adhi; Yashinta Levy Septiarly (Universitas Batanghari Jambi, 2023)
This study aims to find out the extent to which the variabels of Emotion Regulation Self awareness can predict Anxiety. The emotion regulation variabel was measured by an emotion regulation scale based on Thompson's theory (2017), a self-awareness scale based on Morin’s theory (2016) and a counseling anxiety scale based on Stuart's theory (2016). The research was conducted on the support buddy community, LISA Helpline, Bali Province with 113 research samples. The analytical method used is multiple linear regression. The results showed that the variabels of emotion regulation and self awareness can predict anxiety in support buddy.